Labor market discrimination – are women still more secondary workers? - Rembeza, Jerzy; Radlińska, Kamila (Journal of Business Economics and Management, 2021)
Discrimination based on gender is commonly observed on labor markets, although its scale and symptoms are different with regard to country and are subject to changes over time. Gender-related diverse flows on the labor market constitute one of its symptoms. The paper’s main objective was to answer the question whether women on the labor market were still secondary workers. The analysis was conducted based on general models of flows on the labour market, examining connections between changes in a number of unemployed and changes in a number of employed men and women. There were applied data for eight OECD countries from various regions of the world. The obtained results were highly diversified depending on the analysis period and country. However, they confirmed that in the past women had been more secondary workers despite no differences in the unemployment rate. Gender impact was noticeable especially in the employment decrease periods. For data after the year 1990, gender-related differences disappeared or significantly decreased in four countries (Australia, Denmark, United Kingdom, United States), but in two of them (Canada, South Korea) – differences increased. First published online 29 October 2020